Réponses

2014-02-07T16:03:14+01:00
A=(15/14)-(6/7)*(2/3)=(15/14)-(2*3/7)*(2/3)=(15/14)-(2/7)*2=(15/14)-(4/7)=(15/14)-(8/14)=7/14=1/2

B=(1-(7/18))/(7/9)=((18/18)-(7/18))*(9/7)=(11/18)*(9/7)=(11/2*9)*(9/7)=(11/2)*(1/7)=11/14

C=(3*10^6*6*10^5)/(15*10^7)=(3*6/15)*10^(6+5-7)=(18/15)*10^4=1,2*10^4=12*10^3

D=(3*10^6+6*10^5)/(15*10^7)=(30*10^5+6*10^5)/(15*10^7)=(36*10^5)/(15*10^7)=(36/15)*10^(5-7)=2,4*10^-2=24*10^-3

E=3V(2)-V(50)+2V(18)=3V(2)-V(2*25)+2V(2*9)=3V(2)-5V(2)+2*3V(2)=4V2

a) P1=2(x+3)=2x+6
P2=2(2+6-x)=2(8-x)=16-2x

b) P1=P2 ---> 2x+6=16-2x
2x+2x=16-6
4x=10
x=10/4
x=2,5